Insectivorous bats selectively source moths and eat mostly pest insects on dryland and irrigated cotton farms. Issue 1 (12th December 2019) - Kolkert, Heidi; Andrew, Rose; Smith, Rhiannon; Rader, Romina; Reid, Nick
Abstract: Insectivorous bats are efficient predators of pest arthropods in agroecosystems. This pest control service has been estimated to be worth billions of dollars to agriculture globally. However, few studies have explicitly investigated the composition and abundance of dietary prey items consumed or assessed the ratio of pest and beneficial arthropods, making it difficult to evaluate the quality of the pest control service provided. In this study, we used metabarcoding to identify the prey items eaten by insectivorous bats over the cotton‐growing season in an intensive cropping region in northern New South Wales, Australia. We found that seven species of insectivorous bat ( n = 58) consumed 728 prey species, 13 of which represented around 50% of total prey abundance consumed. Importantly, the identified prey items included major arthropod pests, comprising 65% of prey relative abundance and 13% of prey species recorded. Significant cotton pests such as Helicoverpa punctigera (Australian bollworm) and Achyra affinitalis (cotton webspinner) were detected in at least 76% of bat fecal samples, with Teleogryllus oceanicus (field crickets), Helicoverpa armigera (cotton bollworm), and Crocidosema plebejana (cotton tipworm) detected in 55% of bat fecal samples. Our results indicate that insectivorous bats are selective predators that exploit a narrow selection of preferred pest taxa and potentially play an important role in controlling lepidopteran pests on cotton farms. Our study provides crucial information for farmers to determine the service or disservice provided by insectivorous bats in relation to crops, for on‐farm decision making. Abstract : Insectivorous bats consumed consistent proportions of Lepidoptera (frequency and abundance) over the cotton‐growing season, despite a pronounced temporal shift in the composition of available arthropod prey orders in cotton crops.